Strategi Kewirausahaan Sosial dalam Mewujudkan Kemandirian Ekonomi Lokal: Studi Kasus Yen Collection di Desa Catakgayam, Jombang - Achmad Arfinanto Arsyadani; Luhur Prasetiyo (Indo Publishing, 2025)
Social entrepreneurship has become an effective strategy to promote economic independence in rural communities. This study aims to analyze the social entrepreneurship strategies implemented by UD Yen Collection in Catakgayam Village, Jombang Regency, and their impact on local economic empowerment. The study employs a qualitative descriptive approach, using primary data from in-depth interviews with the owner of UD Yen Collection and its employees, as well as secondary data from company documents, activity reports, and relevant literature. Data were analyzed thematically through reduction, presentation, and conclusion drawing. The results indicate that UD Yen Collection successfully empowers the community by involving local residents in various production divisions, enhancing technical skills and product innovation, and creating new job opportunities. Sustainability strategies also strengthen the local creative ecosystem, increase community income, and establish Catakgayam Village as a center for metal and wood-based home decor and handicrafts. In conclusion, UD Yen Collection’s social entrepreneurship practices create a synergy between economic and social values, serving as a relevant and sustainable model for community empowerment.